Analisis Kebijakan Pemberian Pesangon sebagai Bentuk Kompensasi Pasca-Kerja dan Dampaknya terhadap Keharmonisan Hubungan Industrial di Era Omnibus Law - Oki Iqbal Khair; Ahmad Rahadian Danan Nugraha; Irma Fatmawati; Aysha Putri Irawan; Via Aulia Zahra; Muhammad Fadli Fadila; Lilis Syafitri; Emanueli Gulo (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to systematically analyze the implementation of severance pay policy as a manifestation of post-employment compensation and its profound impact on the harmony of industrial relations within the regulatory framework of the Omnibus Law in Indonesia. Utilizing a Systematic Literature Review (SLR) methodology aligned with the PRISMA framework, this research comprehensively synthesizes data from 25 selected academic articles encompassing human resource management, employment law, and organizational behavior. The findings reveal that the paradigm shift from the previous labor regulations to the Omnibus Law framework has fundamentally altered the calculation mechanisms and statutory floors for severance pay. While these legislative adjustments are strategically designed to enhance organizational agility and mitigate financial distress for corporations, they have engendered substantial apprehension among the workforce regarding the degradation of normative rights. Consequently, this policy transformation presents a critical challenge to sustaining industrial harmony, frequently precipitating labor disputes, diminishing employee morale, and intensifying bipartite conflicts. This study recommends that human resource practitioners proactively develop transparent communication strategies and design complementary post-employment benefit architectures to restore distributive justice. Furthermore, policymakers are urged to institute robust oversight mechanisms to ensure equitable implementation and safeguard worker welfare without compromising long-term business sustainability.